Front Stage and Backstage on Instagram: A Phenomenological Study of Female Students' Self-Image Duality Through Second Accounts - Ade Irma; Fitri Meliya Sari; Hanifah Nurdin (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze the duality of self-image of female students of the Faculty of Da'wah and Communication, Universitas Islam Negeri Ar-Raniry through the use of second accounts on Instagram. This self-image duality refers to the difference in the way participants present themselves in the main account and the second account. The main account is generally used to display an ideal, professional, and socially appropriate self-image, while the second account becomes a more personal, authentic, and free space from social pressure. The research uses a qualitative approach with phenomenological methods to explore the subjective experiences of participants. Data was collected through in-depth interviews and digital observations of content uploaded on both accounts. The research participants were selected purposively, namely active female students aged 18–25 years who have and use the main account and second account actively. Thematic analysis techniques are used to identify key patterns and themes in the data. The results of the study show that the use of the main account reflects the concept of the front stage, where participants display their ideal self-image and meet social expectations. In contrast, the second account represents the backstage, where participants feel more free to express themselves without pressure. In addition, second accounts are also used as a means of maintaining privacy, establishing closer relationships, and managing social pressure. The use of second accounts provides space for female students to navigate the duality of self-image, creating a balance between privacy and freedom of expression on social media.